2019
DOI: 10.5194/nhess-19-1619-2019
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Preliminary hydro-meteorological analysis of the flash flood of 20 August 2018 in Raganello Gorge, southern Italy

Abstract: Abstract. On 20 August 2018 a flash flood affected the Raganello Creek (southern Italy) causing 10 casualties. The rainfall event was so highly localized that the spatial coverage of rain gauges were inadequate to measure it, while radar products showed a storm cell with rain peaks of about 70–100 mm h−1. This scientific report provides a preliminary hydro-meteorological analysis of the event and evaluates the forecasting skills of a system based on the WRF–WRF-Hydro models, using both one-way and fully couple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…Several studies show that for short simulations such as those performed in this study it is very difficult that differences emerge in the precipitation fields due to the differences in soil moisture conditions. Among them, Avolio et al (2019), which for a case study rather similar to those analyzed by the authors found that correct SST representation is much more impacting. Therefore, more details should be provided by the authors about how they reached their results, and they should try to explain the reasons they got these results.…”
Section: Main Commentsmentioning
confidence: 68%
“…Several studies show that for short simulations such as those performed in this study it is very difficult that differences emerge in the precipitation fields due to the differences in soil moisture conditions. Among them, Avolio et al (2019), which for a case study rather similar to those analyzed by the authors found that correct SST representation is much more impacting. Therefore, more details should be provided by the authors about how they reached their results, and they should try to explain the reasons they got these results.…”
Section: Main Commentsmentioning
confidence: 68%
“…Norway, despite its high latitude, has a diverse range of climates, including northern Arctic, central alpine and southern maritime, and can exhibit an equally wide range of snow regimes (Pall et al, 2019). The role of snowmelt and rainfall is highly relevant for the seasonal flood regimes (Barnett et al, 2005;Vormoor et al, 2016). For example, south-central Norway has an alpine climate, which receives large amounts of precipitation as snowfall, approximately 30 % (Saloranta, 2012), and has high discharge dur- ing spring and early summer due to snowmelt.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, both as an additional comparison and with the aim of highlighting its relative impact with respect to the effects of different boundary conditions provided by different GCMs and/or more detailed SST fields, a data assimilation technique is also used for both of the test cases. Specifically, a 3D-Var assimilation scheme (Barker et al, 2004;Huang et al, 2009;Barker et al, 2012) is adopted, introducing conventional meteorological observations into the initial conditions and adjusting boundary conditions to improve simulation performance.…”
Section: Wrfmentioning
confidence: 99%